Kesarevo Kesarju Scritti in onore di Cesare G. De Michelis - CICCARINI, MARINA; MARCIALIS, Nicoletta; ZIFFER, Giorgio (Biblioteca di Studi Slavistici, 2014)
This collection of studies is dedicated to Cesare G. De Michelis for his seventy years. It contains contributions by friends and students wishing to recall his teaching and research, together with the variety and breadth of his interests. This explains the heterogeneity of the contributions, which focus primarily on Russian literature but also extend to other Slavic literatures, and then to Russian religious and secular history, to cultural relations between Italy and Russia and to some pages of the modern anti-Semitism. The volume opens drawing a profile and the bibliography of professor De Michelis, including his vast scientific production and a dense list of publicity contributions in which the rigour of the scholar and his civil passion are reflected.